Apoptosis of peripheral blood lymphocytes in Parkinson patients - Màtil Calopa (Neurobiology of Disease, 2010)
Neuronal cell death by apoptosis is a mechanism involved in Parkinson's disease and indirect signs of apoptosis have been found in brain neurons and blood lymphocytes. The present study was aimed to directly assess the presence of enhanced apoptosis in lymphocytes from 89 idiopathic Parkinson's disease patients, 33 untreated and 56 treated, compared with 33 healthy individuals. The study of both spontaneous and activation-induced apoptosis of T-lymphocyte subsets by annexin-V binding and flow cytometry showed that Parkinson patients increased the expression of Fas in circulating CD4+ T cells, mainly “naive,” that correlated with the decrease of these cells in blood. Spontaneous and activation-induced apoptosis of CD4+ T-cell subsets were also significantly increased. Thus, in Parkinson patients, peripheral blood CD4+ T cells have an increased susceptibility to apoptosis with Fas involvement. This fact explains the decrease in the number of CD4+ T-cell subsets observed in Parkinson and could be related to the neurodegenerative process.